(3GdeSFhdjI GdeOfjI dWHj`H GdJNOj`Q (B: s (3OQGSI ebGQfI (B/ s - (3CSeGA ESeGYjd GdSjO ceGd GdOjfs; (3LGHQ eMLhH Ydi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3YGdLJ gPg GdQSGdI ehVhY GdeSFhdjI GdeOfjI dWHjH GdJNOjQ HCSdhH GdHMK GdebGQf Hjf cd ef GdbGfhf GdeUQi h GdbGfhf GdaQfSi(B: (3aGfbSeJ Edi HGHjf(B: (3JfGhd GdChd efgeG eSFhdjI WHjH GdJNOjQ ai fWGb GdeSFhdjI Yf aYd GdZjQ(B: (3h Pdc HHjGf eSFhdjI GdLQGM Yf aYd WHjH GdJNOjQ(B: (3eY JQLjMfG dacQI EVaGA GdTNUjI GdeYfhjI Ydi GdaQjb GdWHi(B: (3ceG CTQfG Edi GdMGdGJ GdJi jecf Cf jSCd ajgG GdeSJTai GdNGU Yf aYd gPG GdWHjH(B: (3h HHGH KGf JMOKfG Yf GdeSFhdjI GdTNUjI dWHjH GdJNOjQ HOGjI ef GdJaQbI Hjf GdeSFhdjI GdYbOjI h GdJbUjQjI dgPG GdWHjH(B: (3eY HjGf WHjYI GdJRGe WHjH GdJNOjQ YeG EPG cGf GdJRGkeG HHPd YfGjI Ce HJMbjb fJjLI(B: (3h GfJgGkA Edi eSFhdjJg Yf GdGSJYGfI HGdeSGYOjf h Jdc GdfGTFI Yf GSJYeGd GdCOhGJ h GdeYOGJ GdWHjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2018s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B414-447s
Keywords: (3GdbGfhf GdeOfjs; (3GdeSFhdjI GdWHjIs; (3GdaQjb GdWHjs; (3WHjH GdJNOjQ s; (3eSFhdjI GdeJHhYs; (3GdCNWGA GdeGOjIs; (3GdCNWGA GdafjIs; (3UjGfI GdLgGR GdWHjs; (3GdcPH GdWHjs; (3WHjYI GdJRGe WHjH GdJNOjQs; (3eSCdI GdJHYjI GdYQVjIs; (3COhGJ GdJNOjQs; (3GdCLgRI hGdefJLGJ GdWHjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs